Sago Starch and its Acrylamide Modified Products as Coating Material in Recycled Paper - Wong, Sin Yeng (2001)
Starches are usually used in recycled paper to improve the paper strength properties. Apart from the common starches available in the market, sago starch offers another alternative since it is cheaper. This study was carried out to determine the suitability of sago starch as paper additive. The basic properties i.e., pH, viscosity and solid content, of the unmodified (4%, 5% and 6% w/v basis) and modified sago starch [sago starch blended with acrylamide (38.5% grafting efficiency), sago starch grafted with acrylamide in an acidic condition and sago starch grafted with acrylamide in an alkaline condition] were determined. The starches were then used to coat laboratory made recycled papers. Various effects were studied, namely, starch concentrations, methods of sago starch modification, addition of different types of initiator and further curing at different temperatures. Increasing the concentration of the unmodified sago starch solutions from 4% to 6% caused significant reduction in their pH values and increased both the viscosity and solid content of the solutions. The unmodified sago starch solution was very viscous (>447 mPa.s) and were susceptible to biological attack after two days at ambient. The incorporation of acrylamide into sago starch through blending or grafting significantly reduced the viscosity of the solutions. All the modified starches remained biologically resistant even after 14 days of exposure to ambient.